The Effect of Arbuscular Mycorrhizae and the Percentage of Lapindo Mud Media on the Growth and Production of Kangkung Darat (Ipomoea Sp.) - Abdul Hakim; Saiful Arifin (Universitas Muhammadiyah Sidoarjo, 2014)
Lapindomud has been being a problem, especially in agriculture area. Special treatments are needed in using Lapindo mud, one of them is mixed Lapindo mud with soil.Not only supports plant growth, but also mycorrhiza form a mutualistic relationship with plant on critical and damaged land. This research aimed to study about interactions and effect ofLapindo mud and arbuscular mycorrhizal on kangkung(Ipomoea sp) yield. The experiment was conducted on May to June 2014. Factorial design was arranged as Randomized Block Design with each treatment using Lapindo mud 0%, 20%, 30% and without the addition of mycorrhizal and repeated 3 times. Variable were plant length, number of leaves, stem diameter, root length, stover fresh and dry weight, yield of fresh components and dry weight.Data obtained in this research were analyzed by ANOVA, then followed by HSD 5%. The results data of administration of mycorrhiza and percentages Lapindo mud showed that real interaction to the number of leaves (M1L1) with results of 9.22. In the provision of mycorrhiza was significantly different at the plant lenght (27.22), stem diameter (0.47) and dry weight (1.27) plant that is on the media by giving mycorrhiza (M1). While the media Lapindo mud percentage was significantly different to the length of the plant (30.63), number of leaves (14.39), stem diameter (0.48), the weight of the wet stover (7.87), dry weight (1.27), root fresh weight (2.87), and root length (22.64) plant on media Lapindo mud percentage of 0% (L0).